THE HISTORIAN AS A PUBLIC MORALIST: ON THE ROMAN ORIGINS OF A SCHOLARLY PERSONA. Issue 2 (13th June 2019) - Paul, Herman
ABSTRACT: In her recent book, Virtus Romana, Catalina Balmaceda provides a fascinating analysis of the concept of virtus in Roman historiography. Although virtus, which translates as courage or more generally as virtue, meant different things to different Roman historians, Balmaceda shows that disagreement was never about whether historians should provide readers with examples of virtue. Historians' differences of opinion focused rather on where such models were to be found and what they should look like. This review essay summarizes Balmaceda's main arguments, raises a question about historians' own virtus, and draws some implications from the book for the study of scholarly personae. Did the persona of the historian as a public moralist, such as is known from nineteenth‐century Europe, originate in ancient Rome?